Development of e-services through projects – case study - Krasiński, Marek; Krzos, Grzegorz (Management Sciences, 2015)
The aim of this paper is to identify the role of projects in the development of innovative company on the example of selected innovative enterprises from Lower Silesia. The enterprise selected for the research was the Samorządowy Informator SMS Sp. z o.o., which provides five main e-services. Each of those was designed basing on project management methodology and is a response for the market needs. The article presents the development of selected e-services and the enterprise development that could be reached through these e-services. Orientation for projects is one of the pillars to implement company’s strategy. The analysis of the enterprise indicates that ability to create e-services as well as effective project portfolio management helps in company’s development on a competitive market
Nauki o Zarządzaniu = Management Sciences, 2015, Nr 2 (23), s. 64-73
Keywords: e-service; project management; communication; SMS; information; e-usługi; zarządzanie projektami; komunikacja; informacje